YOKENELLA REGENSBURGEI osteoarticular infection: a case report - Oliveira Guilarde, Adriana; TELES FILHO, RICARDO VIEIRA; da Mata Padilha, Daniella; Vieira Mendes, Aderrone; Tiemi Matsunaga, Kely; Kipnis, André; Rocha Romão Godoi, Ariana (Revista de Patologia Tropical / Journal of Tropical Pathology, 2021)
Yokenella regensburgei belongs to the family Enterobacteriaceae and is an opportunistic agent rarely associated with infections in humans. We report a case of osteoarticular knee infection caused by Y. regensburgei in a patient under treatment for rheumatoid arthritis, using corticosteroids, with complication in primary total arthroplasty of the knee. Y. regensburgei was identified using the VITEK2 system. Antimicrobial susceptibility testing was performed using the disk-diffusion method, according to the guidelines from the Clinical and Laboratory Standards Institute. The patient presented favorable clinical evolution after the second debridement, with complete removal of the prosthesis and antibiotic therapy with sulfamethoxazole/trimethoprim. This is the first case of Y. regensburgei infection described d in Brazil. KEY WORDS: Yokenella regensburgei; osteoarticular; infection; sulfamethoxazole; trimethoprim; prosthesis.